2010
DOI: 10.1186/1471-2415-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of latanoprost/timolol fixed combination in patients with glaucoma or ocular hypertension: A prospective, observational, noninterventional study

Abstract: BackgroundProspective, observational studies that enroll large numbers of patients with few exclusion criteria may better reflect actual ongoing clinical experience than randomized clinical trials. Our purpose was to obtain efficacy and safety information from a cohort of subjects exposed to latanoprost/timolol fixed combination (FC) for ≥18 months using a prospective, observational design.MethodsIn all, 577 office-based ophthalmologists in Germany switched 2339 patients with glaucoma or ocular hypertension to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 26 publications
8
22
0
Order By: Relevance
“…Numerous studies49 have reported a lack of serious adverse reactions, which is consistent with our findings in this study. Moreover, in the metaanalysis, the fixed-combination eyedrops were associated with a lower risk of hyperemia than the concomitantly used eyedrops 8.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies49 have reported a lack of serious adverse reactions, which is consistent with our findings in this study. Moreover, in the metaanalysis, the fixed-combination eyedrops were associated with a lower risk of hyperemia than the concomitantly used eyedrops 8.…”
Section: Discussionsupporting
confidence: 93%
“…This is evident in the observed IOP lowering effect and unrecorded adverse outcomes in our study population. This finding is in accordance with the reports of several prospective and randomized clinical trials where the combinations of latanoprost/timolol havedemonstrated effectiveness and tolerability [17][18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has demonstrated that progression of glaucoma or ocular hypertension can be delayed or halted by lowering IOP levels through the use of ocular hypotensive agents [14].…”
Section: Discussionmentioning
confidence: 99%